KORELASI ANTARA KETERAMPILAN DENGAN KARAKTER BERFIKIR KRITIS DAN HASIL BELAJAR FISIKA SISWA DALAM PEMBELAJARAN BERBASIS PROBLEM BASED LEARNING (PBL) KELAS X SMAN 5 PADANG - Sri Nicki Yulia (PILLAR OF PHYSICS EDUCATION, 2014)
Low of student`s learning outcomes in physics subject predicted due to the underdevelopment of its critical thinking skills. So, it needed some effort to develop critical thinking skill by applying the deemed appropriate strategy to develop the ability to critical thinking by adopt a strategy of Problem Based Learning (PBL). The purpose of this research is to investigate  the relationship between critical thinking skills with the characters in the PBL-based learning in class X SMAN 5 Padang, and relationship between the character of critical thinking to student learning result in PBL-based learning in class X SMAN 5 Padang. Type of this research is "Correlational". The population of this research is the Tenth graders of SMAN 5 Padang enrolled in the academic year 2013/2014 as much as 5 classes. Sampling was carried out in two stages, the first stage with Porposive Sampling, and the second stage cluster random sampling. Instrument that is used to test to critical thinking skills is CCTST, and questionnaires CCTDI for critical thinking character. Statistics used were Pearson Product Moment Correlation.. For the critical thinking skills versus critical thinking character by using t test analysis, obtained t = 2,854 and t  table = 2.04 at significance level 0.05, it means t-test is outside the reception area of Ho, then Ha is accepted by the correlation coefficient obtained was 0,442 with a standard of 5% real meaning. For the coefficient of determination obtained amounted to 19.53% means 19.53% of the character is affected by critical thinking skill. The rest is affected by other factors. The character of critical thinking based on the results of t test analysis obtained t = 2,280 and ttable = 2.04 at significance level 0.05, it means t-test was in the reception area of Ho, then Ha is accepted with a correlation coefficient of 0.376 was obtained with a 5% means that there is a significant relationship between The critical thinking character and learning outcomes. For the coefficient of determination obtained was 14.20%. It can be concluded that the presence of a significant relationship between critical thinking skills and character with learning outcomes in PBL based learning in class X SMAN 5 Padang